Impact test simulation of automotive wheel rim using finite element analysis - Zainuddin, Hikmah (2017)
Computational simulation is convenient, practical and economical; in contrast with experiments that shall involve high cost in order to provide specimen for test repetition. Focusing on the development stage of wheel rim, impact test is purposely made to evaluate the structure reliability when it subjected to a sudden force. During operation, wheels experience shock, forces on bumpy road and maybe a high impact loading due to an accident. A good wheel should be able to preserve and maintain their functions in such awful condition. This study concerns on the 90 degree vertical impact test and 13 degree lateral impact test simulation of wheel rim. The purpose of the work is to study the energy absorbed by wheel rim subjected to dynamic loading and assigned with three different materials, namely Aluminium 6061-T6, Magnesium AM60 and Stainless Steel 304L. Wheel rim is modelled using CATIA and exported to ABAQUS for further finite element analysis. The comparison between the 90 degree impact test and 13 degree impact test is studied. In addition, mesh sensitivity analysis has been performed, which covers five different size of wheel rim meshing; 20 mm, 15 mm, 10 mm, 7 mm and 5 mm. Subjected to impact velocity of -22222.2 mm/s and 144 kg mass of steel striker, and it is recorded that the 90 degree impact test absorbed higher energy than 13 degree impact test. In terms of energy absorbed percentage difference, aluminium leads the other materials with 24.40 % followed by magnesium 36.30 % and stainless steel comes in last place with 52.34 %. The main property that related to this plastic collapse problem is the yield strength. Aluminium has higher yield strength than the magnesium and stainless steel with percentage different of 51.85 % and 36.30 % respectively. Due to this material property, the aluminium possessed greater strength in order for it to collapse and thus, greater force is produced for the aluminium wheel rim to deform. Besides, in this research aluminium is analysed to be the best choice material for wheel rim, due to the excellent mechanical properties, durability in operation, acceptable mass and price. From the results of this study, it shows that rim model used in the finite element analysis can be used as a basis platform to study the parameters for wheel changes such as the new materials, thickness, size and pattern of spokes. Holistically, the outcomes of the impacting event are influenced by the material properties, wheel orientation and mesh size implemented.